Fibromyalgia: a neglected stress-related illness in Pakistan - Daniyal Muhammad Alam; Rahmah Muhammad; Muhammad Ashhal Iftekhar (Journal of the Pakistan Medical Association, 2023)
Madam, In Pakistan, cases of stress-related illnesses are on a steady incline. Fibromyalgia is a rapidly growing example of an illness characterized by widespread chronic pain, especially on specific tender points.1 This can be caused by stress, depression, anxiety, or traumatic events present in one's daily life. However, the exact cause is unknown.1 Sleep disturbance, headache, morning stiffness, and fatigue are among the most diagnosed symptoms of Fibromyalgia.1 This illness was found to be high among workers in stressful hospital settings especially the youngest ones.2 In an analysis conducted at Indus Hospital, Karachi, from December 2016 to March 2018, 149 (55.8%) patients of 267 were diagnosed with Fibromyalgia. In this study, stress was found to be the most common factor (56%), followed by disturbed sleep (33%), amongst a variety of other variables (4.5%). ¹ Stress and emotional traumas are usually the triggering factors and are more common in a country like Pakistan, where going to therapy is considered taboo or too expensive unfortunately. As a result of this, fibromyalgia remains undiagnosed in most patients until later in life, when the condition has worsened and becomes much more severe. As far as hindrances in diagnosing Fibromyalgia are concerned, research shows that cost is not one of these obstacles as patients with fibromyalgia visit their physicians much more due to other common illnesses such as diabetes despite a similar physician's fee.3 Diagnosing this disease can be a major challenge in Pakistan. Despite physicians having satisfactory knowledge regarding fibromyalgia, a knowledge gap still exists concerning the various diagnostic criteria.4 Studies have shown that non-pharmacological therapies, especially physical therapy, have increased as an alternate treatment for fibromyalgia in recent years.5 But there is still vast unexplored potential as to the effectiveness of psychological treatments for Fibromyalgia. We should aim to make physical and psychological therapies for fibromyalgia easily accessible and readily available to the public. Awareness amongst medical professionals is essential, as a greater understanding leads to an early diagnosis and more effective treatment of patients. And so, we need further extensive studies to not only spread awareness of this neglected and exacerbating, but also provide a solution to it as well.